Computational model of wound healing: EGF secreted by fibroblasts promotes delayed re-epithelialization of epithelial keratinocytes. Issue 10 (12th September 2018) - Andasari, Vivi; Lü, Dongyuan; Swat, Maciej; Feng, Shiliang; Spill, Fabian; Chen, Li; Luo, Xiangdong; Zaman, Muhammad; Long, Mian
Abstract : It is widely agreed that keratinocyte migration plays a crucial role in wound re-epithelialization. Abstract : It is widely agreed that keratinocyte migration plays a crucial role in wound re-epithelialization. Defects in this function contribute to wound reoccurrence causing significant clinical problems. Several in vitro studies have shown that the speed of migrating keratinocytes can be regulated by epidermal growth factor (EGF) which affects keratinocyte's integrin expression. The relationship between integrin expression (through cell–matrix adhesion) stimulated by EGF and keratinocyte migration speed is not linear since increased adhesion, due to increased integrin expression, has been experimentally shown to slow down cell migration due to the biphasic dependence of cell speed on adhesion. In our previous work we showed that keratinocytes that were co-cultured with EGF-enhanced fibroblasts formed an asymmetric migration pattern, where, the cumulative distances of keratinocytes migrating toward fibroblasts were smaller than those migrating away from fibroblasts. This asymmetric pattern is thought to be provoked by high EGF concentration secreted by fibroblasts. The EGF stimulates the expression of integrin receptors on the surface of keratinocytes migrating toward fibroblasts via paracrine signaling. In this paper, we present a computational model of keratinocyte migration that is controlled by EGF secreted by fibroblasts using the Cellular Potts Model (CPM). Our computational simulation results confirm the asymmetric pattern observed in experiments. These results provide a deeper insight into our understanding of the complexity of keratinocyte migration in the presence of growth factor gradients and may explain re-epithelialization failure in impaired wound healing.